Roswell Johnson saves the galaxy! - Colfer, Chris, 1990- (Colfer, Chris, 1990- Roswell Johnson, 2025)
"After saving Earth, Roswell Johnson must once again team up with a group of quirky aliens to save the galaxy"-- Provided by publisher.